PENGARUH PENGAWASAN DAN KOMPENSASI FINANSIA TERHADAP DISIPLIN KERJA PADA KARYAWAN DI PT. SENTRA KARYA CAHAYA RAYA DI PEKANBARU - Nadya Eka Putri; Marzolina '; Nuryanti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study held in PT. Sentra Karya Cahaya Raya Pekanbaru. The aim is to analyze the influence of supervision and financial compensation to employees’ discipline. Population are all employees, consist of 61 employees that selected by using cencus method. Variables are supervision, financial compensation and discipline. Data analyzed by using descriptive and multiple linear regression analysis assisted by SPSS 22 for windows.The study reveals that both supervision and financial compensation significantly influence employees’ discipline either partially or simultaneously. Supervision has the stronger effect to employees’ discipline rather than financial compensation.It is recommended to push employees’ discipline up by running a more effective supervision system and some enhancement as well as some adjustments in financial components such as bonus, pension program and adjust salary amount with the newest regional minimum wages regulation.Keywords: Supervision, Financial Compensation and Discipline